Transportation scenario of Black Bengal goats in Gabtoli and Sirajganj markets of Bangladesh - Sakib, Mohammed Nazmus; Hashem, Md. Abul; Rabbani, Md. Kutube; Islam, Md. Shariful; Azad, Md. Abul Kalam (Journal of Advanced Veterinary and Animal Research, 2016)
Objectives: This study was designed to reveal out the present transportation scenario of Black Bengal goats to and from some selected markets in Bangladesh. Materials and methods: A questionnaire survey to know the behavioral parameters and management provisions provided by the farmers was designed to collect necessary information from Sirajganj and Gabtoli markets. The survey was conducted by direct interview with the stakeholders who were directly involved with the transportation of Black Bengal goats from Sirajganj to Dhaka city. Results: The present study showed that 58% adult respondents were involved in goat transportation program, among them 95% were male. Most of the farmers in the markets lacked institutional education (24%) or just completed primary education (41%). Only 27% of the respondents had earlier experience in transporting animals. Transport durations were <6 h (51%), 6 h (39%), and >6 h (10%). The goats were usually transported on foot or by using vehicles. All the respondents were known about planning of animal transportation. About 2, 5, 7 and 5% of animals were suffering from head swinging, stretching, stamping of feet and paralyzed condition during transportation, respectively. During transportation, the animals exhibited idleness (25%), panting (17%), foaming (14%), vocalization (13%) and moving forward (12%). Most of the farmers provided feed (41%), rest (33%) and shelter (24%) during the transportation of the goats. Only 5% farmers hired trained drivers for transportation purpose. About 27% animals were untied and 7% animals ramped during transportation. Besides, there were high percentage of pressure to animals (23%), hitting or kicking animals (19%) and abuse to animals (15%) during transportation. Conclusion: From this study it is concluded that Black Bengal goats became physically unfit during long time transportation although majority of the farmers took proper management practices. Therefore, changes in behavioral responses might be alleviated through creating awareness to animal raiser as well transporter. http://dx.doi.org/10.5455/javar.2016.c129